A new approach to wood protection: Preliminary study of biologically synthesized copper oxide nanoparticle formulation as an environmental friendly wood protectant against decay fungi and termites - Shiny, K. S.; Sundararaj, R.; Mamatha, N.; Lingappa, B. (Maderas. Ciencia y Tecnología, 2019)
Nanoparticles have addressed many challenges in science and technology and wood science research is one such field that has benefitted from application of metal nanoparticles. The metal nanoparticles that are commercially available for wood protection are synthesised by physical and chemical methods which produces toxic by-products and are expensive. The current study deals with a new approach for utilization of metal nanoparticle for wood protection in an ecofriendly and cost effective way. Metal nanoparticles were synthesised using plant extracts that are known to have wood preservative properties. The synergistic effects of the intrinsic property of plant extracts along with the biocidal property of metal nanoparticles were utilized. Copper oxide nanoparticles were synthesised using leaf extracts of Neem (Azadirachta indica), Pongamia (Pongamia pinnata), Lantana (Lantana camara) and extract of orange peel (Citrus reticulata). The effectiveness of the synthesised plant extract and copper oxide nanoparticle formulation is tested against wood decay fungi using agar mixed with the test substance. Graveyard test is employed to assess the effect of the copper oxide nanoparticle formulation against termites. Preliminary results are promising and studies are progressing to develop a stable and environmentally benign wood preservative formulation of metal nanoparticles and plant extracts.